2021
DOI: 10.3389/fphar.2021.750815
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotanshinone I Specifically Inhibits NLRP3 Inflammasome Activation and Protects Against Septic Shock In Vivo

Abstract: The abnormal activation of the NLRP3 inflammasome is closely related to the occurrence and development of many inflammatory diseases. Targeting the NLRP3 inflammasome has been considered an efficient therapy to treat infections. We found that dihydrotanshinone I (DHT) specifically blocked the canonical and non-canonical activation of the NLRP3 inflammasome. Nevertheless, DHT had no relation with the activation of AIM2 or the NLRC4 inflammasome. Further study demonstrated that DHT had no influences on potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Previous studies revealed that tanshinones, the main component of Salvia miltiorrhiza , have been reported to have anti-inflammatory effects and may be the key component for its anti-inflammatory effects (Jiang et al 2019 ; Liu et al 2022 ; Wang et al 2020a ). In addition, Tanshinone IIA and Dihydrotanshinone I have been reported to inhibit the activation of NLRP3 inflammasome and protect against NLRP3-related diseases (Gao et al 2019 ; Li et al 2022c ; Wei et al 2021 ; Xu et al 2022 ). A recent study found that 15 tanshinones (isolated from Salvia miltiorrhiza ) including Tan I inhibited IL-1β secretion, but did not further demonstrate the specificity of the effect of Tan I on NLRP3 inflammasome activation or the mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that tanshinones, the main component of Salvia miltiorrhiza , have been reported to have anti-inflammatory effects and may be the key component for its anti-inflammatory effects (Jiang et al 2019 ; Liu et al 2022 ; Wang et al 2020a ). In addition, Tanshinone IIA and Dihydrotanshinone I have been reported to inhibit the activation of NLRP3 inflammasome and protect against NLRP3-related diseases (Gao et al 2019 ; Li et al 2022c ; Wei et al 2021 ; Xu et al 2022 ). A recent study found that 15 tanshinones (isolated from Salvia miltiorrhiza ) including Tan I inhibited IL-1β secretion, but did not further demonstrate the specificity of the effect of Tan I on NLRP3 inflammasome activation or the mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and detection were carried out in accordance with the conventional protocol described previously (Z. Wei et al, 2021). The protein extract was lysed with 1× loading buffer.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its ability to reverse multidrug resistance and promote vasorelaxation of coronary arteries in rats, DHT has shown promise as a tumor suppressor by inducing cytotoxicity and reducing angiogenesis. Furthermore, DHT has demonstrated anti-inflammatory properties both in vitro and in vivo 26 31 . Potential anti-inflammatory properties of DHT have been reported for acute kidney injury 27 , adipose tissue inflammation 30 and NLRP3 inflammasome 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DHT has demonstrated anti-inflammatory properties both in vitro and in vivo 26 31 . Potential anti-inflammatory properties of DHT have been reported for acute kidney injury 27 , adipose tissue inflammation 30 and NLRP3 inflammasome 31 . Yuan et al 27 demonstrated that DHT exerted anti-inflammatory effects by inhibiting the secretions of inflammatory cytokines and the activation of the NF-κB pathway in vitro and by alleviating LPS-induced acute kidney injury in vitro.…”
Section: Introductionmentioning
confidence: 99%